Obesity-Induced Insulin Resistance Is Mediated by High Uric Acid in Obese Children and Adolescents - Niu, Yang; Tang, Qingya; Zhao, Xuan; Zhao, Xuelin; Mao, Xiaomeng; Sheng, Jinye; Cai, Wei; Feng, Yi (Frontiers in Endocrinology, 2021)
Objective This study aimed to evaluate whether serum uric acid (SUA) plays a mediating role in the development of insulin resistance (IR) in obese children and adolescents. Methods A total of 369 participants aged 4-17 years with obesity who attended the Nutrition Outpatient Clinic for Obesity at Xinhua Hospital from January 2012 to January 2019 were recruited for this retrospective study. We classified participants into two groups on the basis of HOMA-IR values: the low HOMA-IR group (< 3.16) (n = 222) and the high HOMA-IR group (≥ 3.16) (n = 147). Results The univariate analysis found that the high HOMA-IR group had higher BMI, SUA, and fasting insulin (FINS) (P < 0.05). Multiple linear regression analysis and mediating effect analysis indicated that body mass index (BMI) could directly regulate FINS and HOMA-IR (both P < 0.05). The results from the mediating effect analysis found that UA partially played an indirect role in the link between BMI, FINS and HOMA-IR (both P < 0.05) but had no effect on fasting blood glucose (P > 0.05). Conclusions SUA should be investigated in obesity and plays a partial mediating role in insulin resistance induced by obesity in obese children and adolescents.